A geological theory of the convergence culture. Issue 2 (1st June 2016) - Ahn, Sungyong
This paper proposes a 'geology' of the new mediascape as an alternative way of studying today's digital convergence. By geology, I mean a particular physical condition of media platforms, consisting of the lower stratum of fluid atomic particles or binary signals and the upper stratum of cultural sediments as the solidified patterns of these atoms, both of which are circulating through ceaseless re-sedimentation and re-atomization. The discourses of digital convergence that overwhelmed media studies for the first decade of the twenty-first century could be reinterpreted from this geological perspective in relation to such questions; how the old cultural forms that have hitherto solidified into specific physical structures of 'old media' are re-atomized into a series of zeros and ones; and how they are re-sedimented into specific algorithms simulating these old forms. Tracing geological metaphors in the cultural historiography of the early twentieth century's cultural critics, as in works by Siegfried Kracauer, Herbert Marcuse, and Walter Benjamin, this article extends the origin of the convergence culture even to this so-called 'age of technological reproduction' in terms of how the human and technological modes of cultural production have converged upon a geological infrastructure of mediascape. The convergence was in this sense an event that happened between different agents of cultural production, namely humans and non-humans, as much as between different media forms.